Intention to contribute in cash waqf to assist micro entrepreneurs in covid 19 pandemic: applying theory planned behaviour - Abdul Razak, Dzuljastri; Sofian, Fatimah Noor Rashidah Mohd; Zulmi, Syamsu Rizal (2021)
The COVID-19 pandemic has affected the Micro entrepreneur's financial position due to the mandatory lockdown that restricts face to face business. This situation has made them vulnerable because of a drop in daily sales and a shortage in cash flow. Cash waqf is a unique instrument in that the donor can use cash to contribute to society needs. It differs from traditional waqf practices that use the property. This study aims to investigate whether cash waqf can be a means to assist Microentrepreneurs. The study is carried out by analysing the Theory of Planned Behavior (TPB) that explains the relationship between attitude, subjective norm and perceived behavioural control and the intention to use. A survey method will be used to measure the validity of TPB. The results show that attitude and perceived behaviour control have significant relationship with donors’ intention for cash waqf. This result of the study will contribute to the new body of knowledge. Besides, it will also benefit the regulators to assess the usage of Cash waqf for Micro entrepreneurs.